Experimental analysis of geometrical parameters on the performance of an inline jet plate solar air heater. (15th May 2017) - Soni, Akhilesh; Singh, S.N.
Highlights: Experimental study on an inline jet plate solar air heater is demonstrated. TRP decreases and efficiency increases with increase in mass flow rate. Nusselt Number increases with increase in Reynolds number for all configurations. Collector efficiency, TRP and Nusselt number are found to be maximum at Dj /Dh  = 0.07. Correlation shows that jet diameter has strong influence on Nusselt Number. Abstract: An experimental investigation has been carried out to study flow and heat transfer in solar air heater for inline holes inserted between absorber and back plate. The analysis has been carried out for cross flow conditions. The effect of flow and geometrical parameters, especially jet diameter and hydraulic diameter has been studied. Mass flow rate for the study is varied corresponding to the Reynolds number range of 4600–12, 000. The jet diameter, streamwise pitch, and spanwise pitch, each normalized by hydraulic diameter, i.e. Dj /Dh, X/Dh, and Y/Dh, are in the range: 0.053–0.084, 0.53–0.63, and 0.53–0.63 respectively. Performance is studied in terms of Temperature Rise Parameter (TRP), collector efficiency, and Nusselt number. Hourly variations of solar intensity have also been shown. Collector efficiency increases and Temperature Rise Parameter decreases with increase in mass flow rate for all geometrical configurations. All the above-listed performance parameters are found to be maximum at jet diameter to hydraulic diameter ratio of 0.07. A correlation for Nusselt number in terms of Reynolds number, jet diameter, and hydraulic diameter has also been developed.